1996
DOI: 10.1074/jbc.271.43.26508
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Site Specificity of Pyridinoline and Pyrrole Cross-links in Type I Collagen of Human Bone

Abstract: Compared with soft tissue collagens, bone type I collagen displays a distinctive pattern of covalent cross-linking, with evidence of preferred sites of molecular interaction and a prominence of both immature, divalent crosslinks and mature, trivalent cross-links in the adult tissue. In this study the site-specificity of the mature cross-links in human bone collagen was examined. Peptides containing fluorescent pyridinoline cross-links and Ehrlich's-reactive pyrrole cross-links were isolated from a bacterial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
129
2
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(136 citation statements)
references
References 39 publications
3
129
2
2
Order By: Relevance
“…Enzyme digests of decalcified bone matrix have been used in attempts to isolate pyrrole-containing peptides, but because these peptides are reduced in size and enriched, the pyrrole tends to oxidize or polymerize. 1 In a recent study, Ehrlich chromogen-containing peptides were enriched and analyzed by mass spectrometry, revealing peaks that were interpreted to be derived from peptides containing oxidized pyrrolic cross-link (11). These experiments supported previous preliminary indications that the pyrroles were concentrated at the N-telopeptide site.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Enzyme digests of decalcified bone matrix have been used in attempts to isolate pyrrole-containing peptides, but because these peptides are reduced in size and enriched, the pyrrole tends to oxidize or polymerize. 1 In a recent study, Ehrlich chromogen-containing peptides were enriched and analyzed by mass spectrometry, revealing peaks that were interpreted to be derived from peptides containing oxidized pyrrolic cross-link (11). These experiments supported previous preliminary indications that the pyrroles were concentrated at the N-telopeptide site.…”
supporting
confidence: 66%
“…A similar affinity chromatography approach was used to demonstrate that Ehrlich chromogen cross-links were present at the same loci as the pyridinium cross-links in bovine tendon (10). This work culminated in a proposed structure and mechanism of formation for pyrroles analogous to that for pyridinium cross-link formation: this mechanism involves reaction of a difunctional, keto-imine cross-link with a lysyl aldehyde-derived component rather than a hydroxylysyl aldehyde-derived component (10), where the latter may be a second difunctional cross-link (11). Taken together, these studies suggest that Ehrlich chromogens exist in many different tissues and probably have different chemistries based on their stability and the different spectra observed upon reaction with p-dimethylaminobenzaldehyde (9).…”
mentioning
confidence: 97%
“…MLBR 3 extends from helical residue 920 to the end of the helical region. The gly910-964 stretch of lethal mutations includes one of the two major residues for intermolecular collagen cross-linking (the lysyl residue at helical position 930) [Hanson and Eyre, 1996], as well as sites important for the binding of the decorin proteoglycan core protein , the glycosaminoglycan heparin [San Antonio et al, 1994;Sweeney et al, 1998], and possibly the DDR2 receptor [Schlessinger, 1997;Shrivastava et al, 1997;Vogel et al, 1997]. MLBR 1 is located toward the amino end of the type I collagen helix, where most glycine substitutions are nonlethal.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…Collagen in DBM has also been confirmed to have osteoconductive functions [39]. Hanson et al [40] found that the stereospecific features of bone collagen at the molecular level, such as the pattern of cross-linking and the interchain placement of bonds, were markedly different from other tissue collagens, in particular type I collagen, which may alter collagen mineralization. As BPE is a lyophilisate in collagenous matrix form, consisting of collagen type I chains and other insoluble proteins, the osteoconductive capacity is obvious.…”
Section: Bioactivitymentioning
confidence: 99%
“…In the early 1970s, Bachra [39] verified that bone collagen was a good nucleation catalyst for mineral deposition compared with rat tail collagen. Hanson et al [40] studied the stereospecific features of type I collagen in human bone, which is convenient for collagen mineralization. Although there has been no scientific paper on type I collagen in BPE, it has been documented by the FDA.…”
Section: Composition Analysis Of Bone Protein Extractmentioning
confidence: 99%